Synthesis of Spectral, Thermal and Electrochemical Properties of New Thermally Stable: Blue Light Emitting Materials Based Aromatic Polyamide - Kamil Rashid, Azhar; Binti Yahya, Rosiyah; Sook Wai, Phang (Asian Journal of Chemistry, 2014)
A three new triphenylamine-containing aromatic diacid monomers, 4,4'-dicarboxy-4''-phenoxy-triphenylamine (Ma), 4,4'-dicarboxy-4''-(N-pyrrolyl)triphenylamine (Mb), 4,4',4'',4'''-(1,4-phenylenebis(azanetriyl))tetrabenzoic acid (Mc) were successfully synthesized via the aromatic nucleophilic flouro-displacement reaction of 4-fluorobenzonitrile with aniline-derivatives, respectively using sodium hydride as the base, followed by alkaline hydrolysis of the dinitrile intermediate (Ia),(Ib), (Ic). A series of poly(amine-amide)s were prepared by the direct phosphorylation polycondensation from the newly synthesized diacid monomer with various aromatic diamines. FTIR, 1H and 13C NMR spectroscopic techniques were used to identify the chemical structures of the intermediate dicyano, carboxylic acid monomer and resultant poly(amine-amide)s. These aromatic poly(amine-amide)s were found to be easily soluble in a variety of organic solvents and could afford strong and hard films via solution casting. They exhibited excellent thermal stability associated with high glass transition temperatures (Tg = 246.28-292.62 °C) and 10 % weight loss temperatures in excess of 578 °C in nitrogen. In dilute NMP solution, these polymers exhibited a medium to strong photoluminescence in the blue region at 423-488 nm. Cyclic voltammetry of the poly(amine-amide)s films cast onto an indium tin oxide-coated glass substrate in dry acetonitrile containing 0.1 M of tetrabutylammonium perchlorate (TBAP) as an electrolyte exhibited one oxidation redox couples (Eonset) at (1.32-1.38) V vs Ag/AgCl and revealed electrochromic characteristics with a colour change from pale yellow to blue at applied potentials switched between 0.0 and 1.7 V.